2023
DOI: 10.3389/fimmu.2023.1231813
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum vitamin D concentration with the final course of hospitalization in patients with COVID-19

Klaudia Konikowska,
Katarzyna Kiliś-Pstrusińska,
Agnieszka Matera-Witkiewicz
et al.

Abstract: BackgroundVitamin D deficiency is a substantial public health problem. The present study evaluated the association between vitamin D concentration and hospitalization and mortality risk in patients with coronavirus disease 19 (COVID-19).MethodsThis study used the COronavirus in LOwer Silesia (COLOS) dataset collected between February 2020 and June 2021. The medical records of 474 patients with confirmed severe acute respiratory syndrome 2 (SARS-CoV-2) infection, and whose vitamin D concentration was measured, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…In one randomized prospective trial, patients with COVID-19 and hypovitaminosis D were treated with vitamin D. Restoration of vitamin D levels between 80 and 100 ng/mL was accompanied by significant decrease of ferritin, IL-6, and CRP and increases in the neutrophil-to-lymphocyte ratio [ 25 ]. In one study of 474 patients risk of death by COVID-19 was greater among patients with vitamin D insufficiency [ 26 ]. The results of the recent REsCue trial revealed that treatment with capsules of vitamin D for 2 weeks affected earlier resolution of symptoms only among the subgroup of patients who restored vitamin D circulating levels to normal [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one randomized prospective trial, patients with COVID-19 and hypovitaminosis D were treated with vitamin D. Restoration of vitamin D levels between 80 and 100 ng/mL was accompanied by significant decrease of ferritin, IL-6, and CRP and increases in the neutrophil-to-lymphocyte ratio [ 25 ]. In one study of 474 patients risk of death by COVID-19 was greater among patients with vitamin D insufficiency [ 26 ]. The results of the recent REsCue trial revealed that treatment with capsules of vitamin D for 2 weeks affected earlier resolution of symptoms only among the subgroup of patients who restored vitamin D circulating levels to normal [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that vitamin D supplementation may play a role in the prevention and treatment of COVID-19, as vitamin D deficiency has been linked with an increased risk of acquiring COVID-19 and an increased risk of severe COVID-19 and mortality [19][20][21][22][23][24][25]. Currently, no medicine has been proven effective for treatment of long COVID.…”
Section: Introductionmentioning
confidence: 99%